m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Late Cretaceous bimodal volcanic rocks in Shuanghu induced by lithospheric delamination beneath the Southern Qiangtang, Tibet - Ding-Jun Wen; Xiumian Hu; Timothy Chapman; Gang Zeng; An-Lin Ma; Rui-Qiang Wang (Lithos, 2023)

Examining the effects of station-level factors on metro ridership using multiscale geographically weighted regression - Mengya Li; Mei-Po Kwan; Wenyan Hu; Rui Li; Jun Wang (Journal of Transport Geography, 2023)

Remediation of Pb- and, Cd-contaminated soil through magnetic-modified eluent synergetic freeze-thaw and washing - Yuru Wang; Dahu Rui; Wenjun Nie; Mintae Kim; Daoning Hu; Jun Zhang; Jianfei Liu (Cold Regions Science and Technology, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Quantifying the effects of urban development intensity on the surface urban heat island across building climate zones - Tianxing He; Rui Zhou; Qun Ma; Chunlin Li; Dan Liu; Xuening Fang; Yina Hu; Jun Gao (Applied Geography, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Local eutectic combined with surface functional treatment: An efficient strategy to lower desorption temperature of bulk magnesium-based hydride - Rui Shi; Haoxing Yan; Jiguang Zhang; Yunfeng Zhu; Yana Liu; Jun Wang; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

A new model system for cotton indoor genetic and genomic research - Jun Zhang; Zhanfeng Si; Rui Chen; Wangshu Liu; Yue Shi; Zhuolin Shi; Huan Mei; Yan Hu; Lei Fang; Tianzhen Zhang (Science China Life Sciences, 2023)

The role of Nod-like receptor protein 3 inflammasome activated by ion channels in multiple diseases - Xiaolin Xu; Xianli Wu; Gengyu Yue; Qimin An; Jun Lou; Xiaoxu Yang; Zhe Jin; Jianhong Ding; Yanxia Hu; Qian Du; Jingyu Xu; Rui Xie (Molecular and Cellular Biochemistry, 2023)
The inflammasome is a multimeric protein complex located in the cytoplasm that is activated by many factors and subsequently promotes the release of proinflammatory factors such as interleukin (IL)-1β and IL-18, resulting in a series of inflammatory responses that ultimately lead to the occurrence of various diseases. The Nod-like receptor protein 3 (NLRP3) inflammasome is the most characteristic type and the most widely studied among many inflammasomes. Activation of the NLRP3 inflammasome is closely related to the occurrence of many diseases, such as Alzheimer's disease. At present, a large number of studies have focused on the mechanisms underlying the activation of the NLRP3 inflammasome. Plenty of articles have reported the activation of the NLRP3 inflammasome by various ions, such as K + and Na + reflux and Ca 2+ influx. However, few articles have reviewed the effects of various ion channels on the activation of the NLRP3 inflammasome and the relationship between the diseases caused by these proteins. This article mainly summarizes the relationship between intracellular and extracellular ion activities and ion channels and the activation of the NLRP3 inflammasome. We also provide a general summary of the diseases of each system caused by NLRP3 activation. We hope that more research will provide options for the treatment of diseases driven by the NLRP3 inflammasome.

Abundant rather than rare fungi perform a vital role in maintaining the growth of continuous cropped cut chrysanthemum - Rui Tao; Jun Li; Siqi Yu; Baowei Hu; Ning Ling; Guixin Chu (European Journal of Soil Biology, 2023)

Three decades of organic manure and chemical fertilizers co-application enhanced rice productivity through increasing the diversity and key network module of soil bacterial community - Xiran Zhao; Jun Li; Xin Hu; Baowei Hu; Guixin Chu; Rui Tao (Journal of Soils and Sediments, 2023)

Continuous cropping of cut chrysanthemum reduces rhizospheric soil bacterial community diversity and co-occurrence network complexity - Jun Li; Xiaoyu Cheng; Guixin Chu; Baowei Hu; Rui Tao (Applied Soil Ecology, 2023)

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Yu Liu; Amjad Ali; Jun-Feng Su; Kai Li; Rui-Zhu Hu; Zhao Wang (Science of The Total Environment, 2023)

Rapid and massive fractionation of hemicelluloses for purifying cellulose at room temperature by tetramethylammonium hydroxide - Rui Tian; Bolang Zhu; Qiaoling Liu; Yajie Hu; Ziying Yang; Jun Rao; Yuying Wu; Baozhong Lü; Jing Bian; Feng Peng (Bioresource Technology, 2023)

The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)